Motor and Somatosensory Evoked Potential Monitoring Without Wakeup Test during Scoliosis Surgery - Muhammad Kamran Ayoob , Ammar Dogar , Anum Hafeez , Abdullah Shah , Jamil Ahmed , Amer Aziz, Muhammad Kamran Ayoob , Ammar Dogar , Anum Hafeez , Abdullah Shah , Jamil Ahmed , Amer Aziz (Journal of Rawalpindi Medical College, 2019)
Background: Available evidence suggests that Transcranial electric motor evoked potentials and somatosensory evoked potential are safe methods to check the integrity of the spinal cord during spine deformity correction surgery. We compare the efficacy of Transcranial electric motor evoked potentials and somatosensory evoked potential to detect the nerve injury during Scoliosis surgery. Objectives: To demonstratethe advantages of combined motor and sensory evoked potential monitoring during Scoliosis surgery. Methods: We analyzed records of 65 (48 female and 17 male) Scoliosis surgery cases of Transcranial electric motor evoked potential and Somatosensory evoked potential.Mean age was 15.6 years. Patients who showed significant (at least 55%) of unilateral or bilateral amplitude loss , for at least five to ten minutes during the intervention in scoliosis surgery under total intravenous anesthesia will be included. Results: From 65 patients during surgery seventeen patients have a significant or complete drop of baseline amplitude on transcranial electric motor evoked potentials. Thirteen patients have the complete return of baseline amplitude by surgeon intraoperative intervention, whereas four patients havea reversal of motor response after 8 hours post-operatively. Transcranial electric motor evoked potential monitoring was 100% specific and 100% sensitive, whereas Somatosensory evoked potential was 100% specific and 85% sensitive. Conclusions: SSEPs and MEPs , in combination give accurate and quick information of nerve or spinal cord insult intraoperatively.